MKTG 7 - Lamb, Charles W., 1944-; Hair, Joseph F., 1944-; McDaniel, Carl D., 1942- (South-Western, 2013)
MKTG7 is an engaging and accessible solution to accommodate the diverse lifestyles of today's learners. MKTG7 employs up-to-date, relevant examples from a wide range of independent upstarts and larger companies students love. MKTG7 also offers a dynamic range of web-based review and testing products to facilitate today's on-the-go lifestyle. From chapter by chapter prep-cards and full PowerPoint decks to interactive video quizzing and relevant case-studies, MKTG7 makes reaching out to students a breeze
Keywords: marketing; učebnice; textbooks